Public Speaking Aversion - Thomas Buser; Huaiping Yuan (Tinbergen Institute, 2020)
Fear of public speaking is very common but we know little about its economic implications. We establish public speaking aversion as an economically relevant preference using three steps. First, we use a lab and a classroom experiment to show that preferences for speaking in public vary strongly across individuals with many participants willing to give up significant amounts of money to avoid giving a short presentation in front of an audience. Second, we introduce two self-reported items to elicit preferences for speaking in public through surveys. We show that these items are strongly related to choices in the incentivized lab experiment and that public speaking aversion is distinct from established traits and preferences including extraversion. Finally, we elicit these items in a student survey and show that public speaking aversion predicts students' career expectations, indicating that it is an influential factor in determining career choices.
Keywords: C91; D9; J24; 330; public speaking; validated survey measures; human capital; career choice